WACANA SATIRE POLITIK DALAM AKUN TWITTER @txtdrpemerintah - M. Alvi; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Communication is a message conveyed to the communicant (recipient) from the communicator (source) through certain channels. The Twitter account @txtdrgovernment is a parody account whose content consists of uploading ridiculous quotes from public officials in Indonesia on certain issues that are of public concern. The purpose of this research is to find out the macrostructure, superstructure, and microstructure of Political Satire about cyber attacks on government websites on the Twitter account @txtdrgovernment. This study used a qualitative research method with an approach using the van Dijk model of critical discourse analysis. Data collection techniques consist of interviews, observation, and documentation. While the data analysis technique uses descriptive analysis according to Miles and Huberman. To check the validity of the data using the extension of participation. The results of this study indicate that the @txtdrgovernment account has a macro-structure of political satire about cyber attacks on government websites about the theme of criticism and protests launched after the Bjorka case went viral. Super structure of political satire about cyber attacks on government websites by drafting a tweet starting with a screenshot of mass media coverage in relation to the developments in the Bjorka case and the government's public response. The micro-structure of political satire on cyber attacks on government websites in the @txtdrgovernment Twitter account is divided into: a) Semantics, using comedy satire which is the pattern of communication from the @txtdrgovernment account; b) Syntax, using sentences or words that are not commonly used by the public; c) Stylistic, with the choice of the word